Epidemiological Analysis and Geographical Distribution of Patients Suffering from Rheumatoid Arthritis, Eligible for First-Line Therapy/Monotherapy Treatment with Subcutaneous Formulation of Tocilizumab in the Republic of Macedonia - Gucev, Filip; Perchinkova-Mishevska, Snezana; Bozinovski, Georgi; Irena Kafedjiska; Antova, Dubravka; Damjanovska-Krstic, Ljubinka; Osmani, Bashkim; Hadjihamza, Fjola; Nikolov, Oliver (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2018)
Rheumatoid arthritis is an inflammatory arthritis characterized by synovial tissue inflammation that leads to structural damage and disability. There are several treatment options available, which include glucocorticoids, DMARDs and biologics given alone as monotherapy or in a variety of combinations. Recent evidence has shown that early treatment is important in reducing the rate of progression of erosions and decreasing disability. The lack of adequate statistical data on number of patients that are eligible for first-line therapy/monotherapy of rheumatoid arthritis in Macedonia, triggered this epidemiological analyse describing eligible patients for first-line treatment/monotherapy distributed by gender, age and geographical allocation. The study was conducted by fulfilling a tailored questionnaire every two months in a period of six months (September 2017-February 2018) by including summarized data not related to personal data of patients nor specific drug information. The results have shown that a total of 115 patients in Macedonia are eligible for first-line therapy, whereby 54 (46%) patients were eligible for monotherapy of rheumatoid arthritis. Precise determination of these data provides patients' determination by geographical allocation and proper selection of the best treatment option and optimized therapy for each patient, furthermore when subcutaneous formulation of tocilizumab is available as an effective clinically proven treatment option for RA.